A 220,000-year-long continuous large earthquake record on a slow-slipping plate boundary - Lu, Yin; Wetzler, Nadav; Waldmann, Nicolas; Agnon, Amotz; Biasi, Glenn P.; Marco, Shmuel (Science advances, 2020)
Large earthquakes (magnitude ≥ 7.0) are rare, especially along slow-slipping plate boundaries. Lack of large earthquakes in the instrumental record enlarges uncertainty of the recurrence time; the recurrence of large earthquakes is generally determined by extrapolation according to a magnitude-frequency relation. We enhance the seismological catalog of the Dead Sea Fault Zone by including a 220,000-year-long continuous large earthquake record based on seismites from the Dead Sea center. We constrain seismic shaking intensities via computational fluid dynamics modeling and invert them for earthquake magnitude. Our analysis shows that the recurrence time of large earthquakes follows a power-law distribution, with a mean of 1400 ± 160 years. This mean recurrence is notable shorter than the previous estimate of 11,000 years for the past 40,000 years. Our unique record confirms a clustered earthquake recurrence pattern and a group-fault temporal clustering model, and reveals an unexpectedly high seismicity rate on a slow-slipping plate boundary. - A 220-ka-long Mw ≥ 7.0 earthquake record reveals an unexpectedly high seismicity rate on a slow-slipping plate boundary. - A 220-ka-long Mw ≥ 7.0 earthquake record reveals an unexpectedly high seismicity rate on a slow-slipping plate boundary.
Gesehen am 24.02.2021